2008
DOI: 10.5650/jos.57.115
|View full text |Cite
|
Sign up to set email alerts
|

Lipids in Human Parotid Saliva with Regard to Caries Experience

Abstract: It has been reported that saliva may play an important role in the prevention and development of enamel caries and that both lipids and protein contents in saliva may be relevant to this role. This study examined the lipid and protein levels in saliva from individuals differing in caries experience. Female subjects (20 to 21 years old) were used divided equally into two groups, caries-susceptible group (CSG) and caries-resistant group (CRG). Stimulated parotid saliva and stimulated whole saliva were collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
24
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 26 publications
3
24
0
3
Order By: Relevance
“…Lipids may have an important role in the oral ecosystem. Parotid gland saliva contains neutral lipids, glycolipids and phospholipids (Larsson et al , 1996) and their concentration correlates with the caries experience of the individuals (Tomita et al , 2008). Although lipids could serve as possible nutrient source under fasting conditions, free fatty acids released after lingual lipase activity may also have antimicrobial properties (Hamosh and Burns, 1977), providing an additional host mechanism for shaping the oral microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…Lipids may have an important role in the oral ecosystem. Parotid gland saliva contains neutral lipids, glycolipids and phospholipids (Larsson et al , 1996) and their concentration correlates with the caries experience of the individuals (Tomita et al , 2008). Although lipids could serve as possible nutrient source under fasting conditions, free fatty acids released after lingual lipase activity may also have antimicrobial properties (Hamosh and Burns, 1977), providing an additional host mechanism for shaping the oral microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…A targeted salivary metabolite study among adults indicated that lipid and fatty acid profiles differed between caries free (n=22) and caries active adults (n=22) (Tomita et al, 2008). In a study of an unrelated oral disease, periodontitis, Liu et al conducted whole sample untargeted metagenomics of plaque samples.…”
Section: 0 Discussionmentioning
confidence: 99%
“…Our results on the percentage of TFA concur with those from previous studies 18, 21 , showing the highest abundance for 18:1. Other studies found that the most abundant fatty acids were either 16:0 20 or 18:0 19 . However, there is agreement that the 4 most abundant fatty acids in saliva are 16:0; 18:0; 18:1 and 18:2.…”
Section: Discussionmentioning
confidence: 94%